Importance and Challenges in TPNW Ratification: Regional Analysis of Oceania, the Americas, Europe, Asia, and Africa - Rajagukguk, Michael Haratua; Siagian, Ruben (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2024)
The research focuses on the ratification of the Treaty on the Prohibition of Nuclear Weapons (TPNW), which has become an important global issue in international security. The research aims to analyze the factors that influence countries' decisions to ratify the TPNW, as well as to explore the challenges and concerns that individual countries face regarding this issue. The benefits of the research include a deeper understanding of the political, economic, and security dynamics relating to the non-proliferation of nuclear weapons. Results show that complex political and economic interests influence the decision to ratify the TPNW. In Oceania, countries such as Australia and Fiji demonstrated concerns for strategic alliances and regional security. In contrast, smaller countries such as Kiribati and the Marshall Islands prioritized domestic issues and political considerations. In the Americas, the United States rejects TPNWs as contrary to its national security policy, while NATO commitments often bind countries in Europe. In Asia, resistance from nuclear-armed states such as China and India reflects broader geopolitical strategies, while in Africa, many states do not prioritize the issue due to domestic instability. Identified in-depth understanding of how individual states respond to TPNWs in specific contexts. Comparative analysis across regions provides a new perspective in understanding the interaction between foreign policy and non-proliferation issues. The importance of international dialog and a more holistic approach in addressing non-proliferation challenges. Countries' decisions on ratification of the TPNW are highly dependent on their localities and challenges, which include both domestic and foreign policy issues. The TPNW is not only a non-proliferation issue but also reflects the complexity of international relations and national security policies in different parts of the world.